Deglacial to Holocene Ocean Temperatures in the Humboldt Current System as Indicated by Alkenone Paleothermometry. Issue 1 (8th January 2019) - Salvatteci, Renato; Schneider, Ralph R.; Blanz, Thomas; Mollier‐Vogel, Elfi
Abstract: The response of the Humboldt Current System to future global warming is uncertain. Here we reconstruct alkenone‐derived near‐surface temperatures from multiple cores along the Peruvian coast to infer the driving mechanisms of upwelling changes for the last 20 kyr. Our records show a deglacial warming consistent with Antarctic ice‐core temperatures and a Mid‐Holocene cooling, which, in combination with other paleoceanographic records, suggest a strengthening of upwelling conditions. This cooling, during the globally warm Mid‐Holocene, is consistent with an intensification of the Walker Circulation and the South Eastern Pacific Subtropical Anticyclone, indicative of La Niña‐like conditions in the Tropical Pacific. Surprisingly, oxygen contents in the subsurface increased and productivity was low during the Mid‐Holocene, which are at odds with La Niña‐like conditions. This suggests that the Humboldt Current System reacts in multiple ways to a warmer world and may even include a reversal in the present day subsurface deoxygenation. Plain Language Summary: The Humboldt Current System (HCS) located off Peru produces almost 10% of the global fish catch. This high productivity is promoted by the upwelling of subsurface nutrient‐rich water driven by the effect of the winds over the ocean surface. However, the HCS is highly sensitive to climate change, and the effect of continued warming on upwelling dynamics and in consequence for fishery productivity is not known. In the present work we reconstruct changes in upwelling during the last 20 thousand years to understand the mechanisms that drove upwelling changes in the past. For this purpose we use organic molecules preserved in marine sediments that are sensitive to water temperatures. We found cool temperatures during the mid‐Holocene (8 to 4 thousand years ago), a period characterized by global warm conditions, that we infer as an increase in upwelling intensity. Surprisingly, the productivity was low, and the oxygen contents in the subsurface waters were high which is at odds with increased upwelling off Peru. These results indicate that the HCS responds in multiple and unexpected ways to global warming, suggesting that any impact of future global warming on the biological productivity in the HCS remains uncertain. Key Points: Near‐surface temperatures were reconstructed in multiple cores along the Peruvian margin Our data show a deglacial warming consistent with Antarctic ice‐core temperatures and a Mid‐Holocene cooling Strong upwelling during the Mid‐Holocene is associated with a weak Oxygen Minimum Zone and low export production